Research on Hydrogenation Treatment of Plant-based Biomass - Yan, Yuehua (International Journal of Natural Resources and Environmental Studies, 2025)
Biofuels have emerged as a potential substitute for fossil fuels, with production occurring through a range of methods, including physico-chemical processes and other techniques involving biomass. Plant-based biomass has significant potential for biofuel production and holds considerable promise for future applications in the petrochemical industry. Plant-based biomass is composed primarily of two types: lignocellulosic and microalgal. During processing, pyrolysis enhances the efficiency of upgrading; however, the resulting bio-oil contains numerous oxygenated compounds, the presence of which impairs the bio-oil's performance, rendering it unsuitable for direct use as a fuel. Accordingly, the selective utilisation of catalysts for hydrotreating is imperative, as this reduces the oxygen content and enhances the quality of the bio-oil.